S95 Double-blind Multi-centre Randomised Controlled Trial Of Vitamin D3 Supplementation In Adults With Inhaled Corticosteroid-treated Asthma (vidias). (10th November 2014) - Martineau, AR; MacLaughlin, BD; Hooper, RL; Barnes, NC; Jolliffe, DA; Choudhury, AB; Rajakulasingam, RK; Bhowmik, A; Simcock, DE; Grigg, J; Corrigan, CJ; Hawrylowicz, CM; et al.
Abstract : Introduction and objectives: Asthma exacerbations are commonly precipitated by viral upper respiratory infections (URI). Vitamin D insufficiency associates with susceptibility to URI in patients with asthma. A recent vitamin D trial in adults with asthma reported a trend towards reduced exacerbation risk in the intervention arm as a secondary outcome. Trials of vitamin D in adults with asthma with incidence of exacerbation and URI as primary outcome are lacking. We therefore conducted a multi-centre randomised controlled trial of vitamin D3 supplementation in adults with asthma with co-primary outcomes of severe exacerbation and URI. Methods: Two hundred and fifty adults with inhaled corticosteroid (ICS)-treated asthma were allocated to receive six 2-monthly oral doses of 3 mg vitamin D3 or placebo over one year. Co-primary outcomes were time to first severe exacerbation and time to first URI. Sub-group analyses were performed to determine whether effects of supplementation were modified by baseline vitamin D status or genotype for thirty-four single nucleotide polymorphisms in eleven vitamin D pathway genes. Results: Participants were allocated to vitamin D3 vs. placebo in equal numbers; 82% were vitamin D insufficient at baseline. Vitamin D3 supplementation did not influence time to first severe exacerbation (aHR 1.02, 95% CI 0.69–1.53, P = 0.91) or time to first URI (aHR 0.87, 95% CI 0.64–1.16, P = 0.34). The influence of vitamin D3 on co-primary outcomes was not modified by baseline vitamin D status or genotype. Of 16 pre-specified secondary outcomes, only one showed a difference between arms: vitamin D supplementation induced a modest improvement in respiratory quality of life as evidenced by a reduction in mean total score for the St George's Respiratory Questionnaire at 2 months (-3.9 points, p = 0.005), 6 months (-3.7 points, p = 0.038) and 12 months (-3.3 points, p = 0.060). Conclusions: Vitamin D3 supplementation did not influence time to exacerbation or URI in a population of adults with ICS-treated asthma with a high prevalence of baseline vitamin D insufficiency.